Chromosome 3p loss of heterozygosity and mutation analysis of the FHIT and beta-cat genes in squamous cell carcinoma of the head and neck. Issue 7 (July 1998) - González, M V; Pello, M F; Ablanedo, P; Suárez, C; Alvarez, V; Coto, E
Abstract : AIMS: To study the loss of heterozygosity at the short arm of chromosome 3 in primary tumours from patients with squamous cell carcinoma of the head and neck; to determine whether the FHIT gene, mapped to 3p14.2 and the CTNNB1 (beta-cat) gene, mapped to 3p21, are deleted or mutated in these tumours. METHODS: DNA was extracted from fresh tumours. Loss of heterozygosity was assessed by microsatellite analysis of the following markers: D3S1283 and D3S1286 (3p24), D3S966 (3p21), and D3S1300 (3P14.2). Homozygous deletion was determined by radioactive multiplex polymerase chain reaction of exons 5 and 6 of the FHIT gene. The presence of mutations in FHIT exon 5 and beta-cat exon 3 was studied by single strand conformation polymorphism. RESULTS: 50% of informative cases (25/50) showed loss of heterozygosity for at least one of the 3p markers. 3p21 was the region with the highest rate of allelic deletion (63%). No point mutation was found in FHIT exon 5 or beta-cat exon 3. No case showed homozygous deletion for the FHIT (exons 5 and 6) or the beta-cat exon 3. CONCLUSIONS: The short arm of chromosome 3 is often deleted in the head and neck squamous cell carcinomas. In the remaining alleles of the FHIT or beta-cat genes, no evidence was found for point mutations or deletions, documented in other common carcinomas. Inactivation could occur by different mechanisms such as methylation, or other genes (not studied here) could be target of allelic losses in squamous cell carcinoma of the head and neck.